2010
DOI: 10.1364/ol.35.001251
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous beam combination and aperture filling of coherent laser arrays by conjugate Dammann gratings

Abstract: A technique for simultaneous beam combination and aperture filling of a coherent laser array that uses a conjugate Dammann grating is proposed. It can convert light from a coherent laser array into a single-lobed far field with high quality. An experiment with a simulated 5 ϫ 5 2D coherent laser array using an aperture mask has been performed. The feasibility of the proposed scheme is verified. It provides an important basis for achieving a high-power and high-brightness laser beam from an actual coherent lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Swanson et al [23] and Paboeuf et al [24] also demonstrated this method using a He-Ne laser array and a diode laser array respectively, in low power level. Experimental combined efficiency was lower than theoretical efficiency in references [21]- [24]. So, causes leading to loss of the combined efficiency are necessary to be researched in a DG-based aperture filling system, especially in high power phase-locked system.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Swanson et al [23] and Paboeuf et al [24] also demonstrated this method using a He-Ne laser array and a diode laser array respectively, in low power level. Experimental combined efficiency was lower than theoretical efficiency in references [21]- [24]. So, causes leading to loss of the combined efficiency are necessary to be researched in a DG-based aperture filling system, especially in high power phase-locked system.…”
mentioning
confidence: 87%
“…Energy of the input beam is equally split into each diffraction order [20]. Yan et al present an aperture filling technology using a DG [21], [22]. Nevertheless authors of these references split their He-Ne lasers into several beams to imitate a phase-locked laser array (PLA), rather than a practical CBC system.…”
mentioning
confidence: 99%
“…Aperture filling technique using Dammann gratings can eliminate the above mentioned difficulty 6 . By placing a phase plate and a conjugate Dammann grating in the front and back focal plane of a Fourier lens respectively, a coherent laser array can be combined into a single beam.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been used inversely to coherently combine equal intensity laser beam array into one high-power high-quality output beam [3][4][5][6], where the phases of the input phase-locked laser array are modulated by a compensation phase plate (PP) to be exactly the phases of the equal-intensity spot array.…”
mentioning
confidence: 99%
“…When a 64 × 64 DG is used, the PP will be extremely difficult to fabricate. So, in this Letter, we first propose an improved type of DG that produces a spot array which has only three phases (all positive-order phases are equal θ , all negative-orders θ − −θ , and zero order θ 0 ), to simplify the fabrication of the PPs in the DG-based coherent beam combining systems in [3][4][5][6]. Meanwhile, the phase structure of the DG itself is not changed, i.e., the proposed DG still has a (0, π) binary phase structure.…”
mentioning
confidence: 99%